What explains the urban wage premium? Sorting, non-portable or portable agglomeration effects? - Hanna Frings; Rebecca Kamb (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Using administrative data for West Germany, we study the relative importance of different determinants of the urban wage premium. More explicitly, we distinguish worker sorting, as well as portable and non-portable agglomeration effects. Our results indicate that worker sorting explains about two thirds of the urban-rural wage gap. We show that the estimated fraction of the urban wage premium attributed to worker sorting differs considerably depending on the selectivity of the sample used for identification and provide guidance how this selectivity can be reduced. Agglomeration effects explain about one third of the urban wage premium, with portable and non-portable agglomeration effects being of similar importance. – – Anhand administrativer Daten für Westdeutschland untersuchen wir die relative Bedeutung verschiedener Determinanten der städtischen Lohnprämie. Explizit unterscheiden wir zwischen Arbeitersortierung sowie portablen und nicht-portablen Agglomerationseffekten. Unsere Ergebnisse zeigen, dass die Arbeitersortierung etwa zwei Drittel des Lohnunterschieds zwischen Stadt und Land erklärt. Wir zeigen, dass der geschätzte Anteil der städtischen Lohnprämie, der auf die Arbeitersortierung zurückzuführen ist, je nach Selektivität der für die Identifikation verwendeten Stichprobe erheblich variiert und geben Hinweise, wie diese Selektivität reduziert werden kann. Agglomerationseffekte erklären etwa ein Drittel der städtischen Lohnprämie, wobei portable und nicht-portable Agglomerationseffekte von ähnlicher Bedeutung sind.
Keywords: R23; J31; J60; 330; Urban wage premium; sorting; agglomeration